PENGARUH PANHisTEREKTOMI TERHADAP HOMEOSTASIS KALSIUM DAN FOSFOR TIKUS Sprague Dawley YANG DIBERI PAKAN BUNGKIL KEDELAI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The objectives ofthe current experiment were to study the effect ofpanhisterectomy on calcium (Ca) and phosphorus (P) homesotasis in female Sprague Dawley rats that were fed soymeal which ratio of Ca:P 3: 1.Ten female Sprague Dawley rats, 6 weeks of age were randomly divided into two groups of five each. At 8 weeks of age, the rats of treatment group were panhisterectomized. The second group was left as control At 20 weeks of age, all animals of the two groups were placed in to individual metabolic cages for a balance study. Every morning from day 4 to 8 of the balance study, the feed left over was collected for Ca and P analyses. Urine and fecal samples were also collected at the same time. The results showed that fecal Ca and P excretion were significantly higher (P